Memonumentalisasi Perdamaian: Ingatan Pasca-Konflik, Pendidikan Kewargaan, dan Pariwisata Berbasis Komunitas di Ambon, Indonesia - Sillia, Nurul Fadila; Litaay, Simona Christina Henderika; Makaruku, Nathalia Debby (Universitas Pattimura, 2023)
This article analyzes the role of the Ambon Peace Gong as a multidimensional space that integrates post-conflict memory, civic education, and community-based tourism. The study aims to understand how this monument is interpreted, managed, and utilized by local communities, visitors, and stakeholders within the broader context of post-conflict social transformation in Ambon, Indonesia. Employing a qualitative approach and case study method, data were collected through in-depth interviews, participant observation, and document analysis of museum materials and related policies. Thematic analysis was conducted to explore the symbolic, educational, and economic dimensions of the monument. The findings reveal that the Peace Gong functions not only as a reminder of past violence but has also evolved into a social arena that fosters civic values, expands public learning spaces, and creates economic opportunities through tourism rooted in local narratives. The novelty of this study lies in its interdisciplinary approach, viewing the monument as a living site whose meanings and functions are continuously negotiated. This research contributes to the discourse in social sciences and humanities, particularly in the fields of memorialization, peace education, and participatory tourism development, and recommends strengthening community involvement to sustain the relevance and future of peace sites in Indonesia.